Emotional intelligence and autism spectrum disorder - Chaidi, Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
In recent years there has been a growing interest in people on the autism spectrum emotional intelligence, an area in which people with Autism Spectrum Disorder (ASD) show a deficit. The aim of this work is through a literature review of the research a) to illustrate the emotional development and education of individuals on the spectrum and b) to present the findings of eye-tracking, neuro-imaging, and electro-physiological studies in individuals with ASD because they allow researchers, among other things, to discover the mechanisms and how they affect emotion. (c) Raise questions about the development of educational methods aimed at enhancing the emotional development of individuals on the autism spectrum and subsequently the development of social skills.